Fast Holocene slip and localized strain along the Liquiñe-Ofqui strike-slip fault system, Chile - Luis Astudillo-Sotomayor (Nature Portfolio, 2021)
Abstract In active tectonic settings dominated by strike-slip kinematics, slip partitioning across subparallel faults is a common feature; therefore, assessing the degree of partitioning and strain localization is paramount for seismic hazard assessments. Here, we estimate a slip rate of 18.8 ± 2.0 mm/year over the past 9.0 ± 0.1 ka for a single strand of the Liquiñe-Ofqui Fault System, which straddles the Main Cordillera in Southern Chile. This Holocene rate accounts for ~ 82% of the trench-parallel component of oblique plate convergence and is similar to million-year estimates integrated over the entire fault system. Our results imply that strain localizes on a single fault at millennial time scale but over longer time scales strain localization is not sustained. The fast millennial slip rate in the absence of historical Mw > 6.5 earthquakes along the Liquiñe-Ofqui Fault System implies either a component of aseismic slip or Mw ~ 7 earthquakes involving multi-trace ruptures and > 150-year repeat times. Our results have implications for the understanding of strike-slip fault system dynamics within volcanic arcs and seismic hazard assessments.